Characterization of COVID-19 infection in children: A 6 months experience in a tertiary care hospital in Dhaka, Bangladesh (Anwer Khan Modern Medical College Journal, 2023)
Background: Corona virus disease is a global health crisis, a surprising feature of the disease reflects that children might be less affected in the initial stage. Previous studies suggest that COVID-19 more likely to infect adults, but paediatric patients are on the rise. In most of the cases children have mild or moderate symptom of COVID-19, but another new serious presentation emerged named Multisystem inflammatory syndrome in children (MIS-C) which includes features like Kawasaki disease or toxic shock syndrome. The past few months we have seen a lot of findings and variation regarding the COVID-19 illness. As childhood presentation are variable analyzing the pattern of disease in children helps the policy makers to make the better strategies and health care givers to serve better.Objectives: This study was conducted to assess the age and sex distribution, clinical presentations, morbidity, mortality pattern in children with COVID-19 infection.Methods: This descriptive study conducted in the Outpatient Department of Pediatrics and dedicated COVID-19 unit of Anwer Khan Modern Medical College Hospital, Dhaka, Bangladesh from May 2020 to November 2020. 24 children with RT-PCR positive for COVID-19 were included in this study. Medical records of these patients were reviewed and data were analyzed using SPSS software version 20.Results: The total number of children with RT-PCR positive for COVID-19 during the study period was 24. The male female ratio was 1.4:1. Most of the patients were aged over 10 years 9(37.5%). Fever (92%), cough (75%) and headache (50%) were the most common clinical features. A total 10 (41.7%) patients presented with mild clinical symptoms, 6 (25%) were severe to critical state and 2(8.3%) patients found with features with MIS-C. No mortality was observed.Conclusion: The paediatric patients with COVID-19 had mild illness and had good prognosis. The child with MIS-C need early intervention for better outcome.AKMMC J 2021; 12(1) : 45-51